The Effects of Adoptive Knowledge Management Strategy in the Performance of Botswana Water Utilities Corporation - Mzwinila, K. C; Okharedia, A. A. (Archives of Business Research, 2023)
This research attempts to explore the effects of adaptive Knowledge management strategy in the performance of Botswana Water Utilities Corporation. In this research paper, organizational performance is measured under the following: - (a) Customer satisfaction (b) Quality of service (c) Employee attraction and retention. The researcher used mixed methods in investigating the research problem which mainly revolves around the effect of adaptive knowledge management strategy. The findings in the research confirm that the recognition of adaptive knowledge management strategy if well utilized and managed will increase the organization performance in respect of quality of service, customer satisfaction, employee attraction and retention. In addition to the above, the research buttressed the various strategic measures that could be considered by the organization to improve its performance.